Transclass in French Sociology: A Phenomenological Approach to Social Mobility - Šapoka, Kęstutis (Sociologija. Mintis ir veiksmas, 2025)
This article examines a subfield of French sociology that explores and provide phenomenological interpretation of the experience of social transclass—specifically, the transition from one social class to another. It begins by outlining the core conceptual principles of this sociological approach and then examines the internal discussions surrounding transclass discourse, along with the differing perspectives on the very concept of transclass. One of the central issues within this discourse is the relationship between this sociological approach and French literature. The article aims to clarify what sociologists studying transclass seek in certain literary works and how sociological studies of transclass experiences provide meaning and an existential background for literary writing. The analysis of transclass discourse concludes with an examination of its feminist perspective and the ideological dilemmas inherent in this field of sociology.